The Effect of Service Quality and Brand Image on Repurchase Intention With Brand Trust as Mediating Variable By The Generation Z of E-Wallet Consumers in Jakarta - Dwi Asri Ningrum; Mohamad Rizan; Agung Kresnamurti Rivai P (Journal Research of Social Science, Economics, and Management, 2021)
In this digital era, e-wallet is very much needed in various types of online payments, especially for generation. Study to analyzes the variables that affect continuous used of e-wallet by consumers with the intention that they can provide solutions to problems for e-wallet products is needed. This study examines the influence of service quality and brand trust on e-wallet consumer repurchase intention and brant trust as an intervention in Indonesian context. The purpose of this research is to understand the important effects of service quality and brand image on brand trust and its impact on repurchase intention with a case study of generation z of e-wallet consumers in Jakarta. Seven hypotheses are posited and in order to empirically test them, a sample data set of 300 was compiled from Jakarta City of Indonesia with the data collection method used a survey with an instrument in the form of a questionnaire. The data analysis technique used SPSS version 25 and SEM (Structural Equation Model) from the LISREL statistical package version 8.8. The results indicate that service quality and brand image positively influences brand trust as an intervation and impact repurchase intention in a significant way. The interesting things is about managerial implications for increasing repurchase intention from consumers and also limitations and future research directions are suggested. In general, this study immensely contributes new knowledge to the existing body of service quality and brand image literature in e-wallet consumers context that which is still rarely researched in developing countries.